Akibat Hukum Pemalsuan Sidik Jari Pengganti Tanda Tangan dalam Akta Autentik - Adam, Putri Maulia; Purba, Hasim; Suprayitno, Suprayitno; Wau, Hilbertus Sumplisius M. (SIGn Jurnal Hukum, 2024)
This research aims to comprehensively examine the juridical implications of fingerprint forgery as a substitute for signatures in authentic deeds and analyze the judicial considerations in handling such cases, using Decision Number 87/Pdt.G/2014/PN.Kpn as a case study. This normative legal research utilizes a statutory approach and a case study approach. Data analysis employs a qualitative content analysis to describe the problem and answer the research objectives. The results show that fingerprint forgery in authentic deeds has multidimensional legal consequences, covering civil, criminal, and administrative law aspects. In civil law, such a deed has the potential to be null and void due to a defect in the element of consensus, which results in the invalidity of the transfer of rights. From a criminal law perspective, this act constitutes the crime of document forgery. Meanwhile, notary publics or land deed officials involved or who are negligent may be subject to administrative sanctions. The analysis of Decision Number 87/Pdt.G/2014/PN.Kpn shows that the judicial considerations were based on the principles of legal certainty, justice, and benefit while emphasizing the importance of due diligence, integrity, and professionalism, especially for Land Deed Officials in carrying out their duties and functions to ensure the validity and authenticity of authentic deeds.